Principles of designing virtual environments in the educational system and psychological features of their perception by students - Liliya R. Nurtdinova; Maxim V. Gureev; Svetlana V. Krutskaya (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
This article highlights the need to know the principles of designing virtual reality and multi- media products for educational purposes. This need is dictated not only by the rapid technological progress that takes place in all spheres of human life, but also by the positive impact of information technology on the educational component. The learning process increasingly includes IT technology and virtual reality (VR). This leads to the need for proper and qualitative use of these resources in the educational process. In this regard, the authors of the article analyze the basic principles of creating multimedia products and psychological features of the perception of virtual environments. Then a theoretical scheme of the VR based learning environment created in the course of work on the program for studying foreign languages by a group of teachers of SSTU is given. At the end of the article, the authors come to the conclusion that the use of high-tech programs in education includes not only the technical side of developing the program, but also the ability to present the material, taking into account the students’ psychological perception of screen design and virtual environments.